Head and neck pathology - Barnes, Leon, 1941- (Consultant pathology series, 2011)
Head and Neck PathologyThe head and neck is the site of some of the most diverse and histologically complex tumors in the human body. Within this small, highly specialized region, one finds a remarkable range of tissues, including skin, mucosal surfaces, soft tissue, bone, lymph nodes, peripheral and central nervous system tissue, paraganglia, endocrine organs, salivary glands and odontogenic structures. Compounding the issue, biopsies are often small, frequently distorted and difficult to orient for paraffin embedding, all of which impact evaluation and diagnosis, even for experienced patholo.